Effects of Fusarium metabolites beauvericin and enniatins alone or in mixture with deoxynivalenol on weaning piglets. (December 2021) - Novak, Barbara; Lopes Hasuda, Amanda; Ghanbari, Mahdi; Mayumi Maruo, Viviane; Bracarense, Ana Paula F.R.L.; Neves, Manon; Emsenhuber, Caroline; Wein, Silvia; Oswald, Isabelle P.; Pinton, Philippe; Schatzmayr, Dian
Abstract: The impact of the Fusarium -derived metabolites beauvericin, enniatin B and B1 (EB) alone or in combination with deoxynivalenol (DON) was investigated in 28–29 days old weaning piglets over a time period of 14 days. The co-application of EB and DON (EB + DON) led to a significant decrease in the weight gain of the animals. Liver enzyme activities in plasma were significantly decreased at day 14 in piglets receiving the EB + DON-containing diet compared to piglets receiving the control diet. All mycotoxin-contaminated diets led to moderate to severe histological lesions in the jejunum, the liver and lymph nodes. Shotgun metagenomics revealed a significant effect of EB-application on the gut microbiota. Our results provide novel insights into the harmful impact of emerging mycotoxins alone or with DON on the performance, gut health and immunological parameters in pigs. Highlights: Beauvericin, enniatin B + B1 (EB) fed with deoxynivalenol (DON) decreased the piglets weight gain. Exposure to an EB-contaminated diet for 14 days significantly reduced the microbial diversity. Liver enzyme activity was significantly reduced in the EB + DON group after 14 days. All mycotoxin-diets led to different histological lesions in the jejunum, liver and lymph nodes.